Bahasa, Pikiran, dan Budaya: Analisis Semantik Terhadap Fungsi Bahasa Sebagai Alat Komunikasi - Nanda Salsabila; Fitrotin Nisa’; Hawa Kamila Al-Khanifah; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2026)
Language does not only function as a means of exchanging information but also serves as a link that connects individual thought with cultural values. This study aims to explore the relationship between language, thought, and culture from a semantic perspective, with an emphasis on the role of language as a medium for conveying meaning in communication. This research employs a descriptive qualitative approach using semantic analysis of linguistic data consisting of words and phrases that reflect cognitive processes and cultural contexts. The results reveal that language contains implicit meanings influenced by mental structures and cultural backgrounds, which in turn affect how people understand and interpret reality. In addition, the study shows that semantic elements in language play a crucial role in constructing collective understanding within a community. These findings emphasize the importance of semantic analysis in understanding language as a holistic system encompassing communication, thought, and culture.